2008
DOI: 10.1128/aem.00324-08
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Sugar Fermentation and Protein Expression Patterns of Two Lactobacillus plantarum Strains Grown in Three Different Media

Abstract: A comparative study of two strains of Lactobacillus plantarum (REB1 and MLBPL1) grown in commercial medium (MRS broth), cucumber juice, and liquid pig feed was performed to explore changes to the metabolic pathways of these bacteria, using a proteomics approach (two-dimensional electrophoresis and liquid chromatography-tandem mass spectrometry) combined with analyses of fermentable sugars and fermentation end products. The protein expression showed that even with an excess of glucose in all media, both strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…Passos et al (2003), in their research on growth kinetics of L. plantarum MOP-3, found out that the biomass yield coefficient (mg cells/mmol hexoses) was significantly increased while the maintenance coefficient (mmol hexoses/mg cells h) was significantly reduced in the presence of malic acid, indicating that the culture had lower demand for hexoses. Similar results were published by Plumed-Ferrer et al (2008), who compared the growth of two strains of L. plantarum, both in MRS broth and in cucumber juice. They reported that the strains grown in cucumber juice showed relatively low hexose consumption of around 10 %, even though the media contained an excess of glucose.…”
Section: Sugar Consumptionsupporting
confidence: 87%
“…Passos et al (2003), in their research on growth kinetics of L. plantarum MOP-3, found out that the biomass yield coefficient (mg cells/mmol hexoses) was significantly increased while the maintenance coefficient (mmol hexoses/mg cells h) was significantly reduced in the presence of malic acid, indicating that the culture had lower demand for hexoses. Similar results were published by Plumed-Ferrer et al (2008), who compared the growth of two strains of L. plantarum, both in MRS broth and in cucumber juice. They reported that the strains grown in cucumber juice showed relatively low hexose consumption of around 10 %, even though the media contained an excess of glucose.…”
Section: Sugar Consumptionsupporting
confidence: 87%
“…Indeed, the study by Cohen et al reporting the proteomic map of L. plantarum WCFS1, did not give any indication of the expression of PDH complex subunits [40]. Differential proteomic studies on L. plantarum strains, did not show evidence of PDH biosynthesis [41,42]. Coherently, our proteomic data clearly indicated that the A, B and C subunits of PDH were never detectable in the wild type strain, while the biosynthesis of these proteins was triggered by ccpA inactivation, regardless of growth condition.…”
Section: Discussionmentioning
confidence: 90%
“…can be applied in the future (Borneman et al 2010). Proteomic approaches have been used to study the sugar fermentation patterns in L. plantarum (Plumed-Ferrer et al 2008) and the effect of tannic acid on Lactobacillus hilgardii (Bossi et al 2007). Metabolomics have been used to compare the effect of L. plantarum and O. oeni on primary and secondary metabolite production in wine.…”
Section: Introductionmentioning
confidence: 99%